Method for repairing electrolyte of all-vanadium redox flow battery coupled with high-value conversion of biomass

CN122930967APending Publication Date: 2026-10-16HUNAN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610944058.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]针对现有技术的不足,本发明提供了一种全钒液流电池电解液修复耦合生物质高值转化的方法,解决了现有化学还原修复方法存在易引入杂质、释放有害废气且修复不彻底的缺陷,同时常规电解修复过程能耗高且缺乏经济附加值的问题

Benefits of technology

1、本发明通过向失衡的混合电解液中滴加双氧水或臭氧混合物将V(III)全部氧化为V(IV),随后在电解体系中利用恒流电解将阴极电解液的平均价态精确还原至实用的3.5价,这种化学均相氧化结合电催化定量的处理方式,避免了传统添加固相化学还原剂带来的金属杂质离子引入与碳源残存问题,修复后的电解液纯净度高且价态分布精确,能够复原全钒液流电池的初始容量与长循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930967A_ABST
    Figure CN122930967A_ABST
Patent Text Reader

Abstract

The application discloses a method for repairing vanadium redox flow battery electrolyte coupled with high-value conversion of biomass. The method mixes positive and negative electrolyte with mismatched valence states, measures the vanadium ion concentration ratio, adds an oxidizing agent to oxidize all V(III) to V(IV) to obtain a pre-repairing solution; a double-chamber electrolysis system composed of a graphite felt cathode modified by a single-atom catalyst, a supported nickel foam anode and a composite bipolar membrane is constructed; the pre-repairing solution is added to the cathode chamber, and an alkaline aqueous solution containing biomass is added to the anode chamber for constant current electrolysis, and the process is stopped when the average oxidation state of the cathode solution decreases to a practical target valence state of 3.5. The application utilizes chemical oxidation combined with electrolytic reduction mechanism to accurately restore the valence state without introducing impurities; the anode biomass electro-oxidation is used to replace the water decomposition and oxygen evolution reaction, the high-value conversion solution is synthesized synchronously to reduce the energy consumption of system repair, and the combination of battery maintenance and biomass conversion is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vanadium redox flow battery technology, specifically a method for repairing electrolyte in vanadium redox flow batteries and coupling high-value conversion of biomass. Background Technology

[0002] Vanadium redox flow batteries store and release energy through reversible redox reactions of vanadium ions in different valence states within the positive and negative electrode electrolytes. During long-term charge-discharge cycles, due to side reactions such as hydrogen and oxygen evolution within the battery, as well as the transmembrane migration of vanadium ions, the valence state distribution of vanadium ions in the positive and negative electrode electrolytes gradually deviates from its initial state, resulting in valence imbalance. At this point, the imbalanced electrolyte includes V(III) and V(IV) valence states, but they are mismatched, leading to a continuous decrease in the actual usable capacity of the battery system. To maintain the energy storage efficiency of the battery system, the imbalanced electrolyte needs to be periodically repaired.

[0003] Currently, conventional electrolyte repair methods mainly involve directly adding chemical reducing agents such as oxalic acid and ascorbic acid to the imbalanced electrolyte to restore the valence state of vanadium ions. This approach faces several drawbacks in practice. When chemical reducing agents react with strongly acidic electrolytes, they easily generate carbon dioxide gas and acid mist, increasing the equipment requirements for exhaust gas treatment and the risk of environmental pollution. During the addition of solid chemical reagents, it is unavoidable to introduce foreign metal impurity ions and unreacted organic carbon substances into the originally high-purity vanadium electrolyte. These residual impurities accumulate during multiple repair cycles, depositing on the graphite felt electrode surface of the battery and poisoning active sites, thereby exacerbating side reactions in subsequent cycles and making it difficult to fully restore the performance of the repaired electrolyte. Conventional electrolytic repair processes not only require overcoming the high kinetic energy barrier caused by the water desorption and oxygen reaction, consuming a large amount of electrical energy, but the entire maintenance process is also a purely energy-intensive operation, failing to generate other material outputs and economic added value. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a method for the repair of vanadium redox flow battery electrolyte coupled with high-value conversion of biomass. This method solves the problems of existing chemical reduction repair methods, such as easy introduction of impurities, release of harmful waste gases, and incomplete repair. At the same time, conventional electrolytic repair processes have high energy consumption and lack economic added value.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for repairing and coupling high-value conversion of biomass using an all-vanadium redox flow battery electrolyte, comprising the following steps: The positive and negative electrolytes of the vanadium redox flow battery to be repaired are mixed to obtain mixed electrolyte 1, which includes V(III) and V(IV) but the valence states do not match. The molar ratio of V(IV) to V(III) in the mixed electrolyte 1 was determined; Based on the molar concentration ratio, an oxidant is added to the mixed electrolyte 1 to oxidize V(III) in the mixed electrolyte 1 to V(IV) to obtain the pre-repair electrolyte 2; The oxidant is selected from hydrogen peroxide solution, a mixture of hydrogen peroxide solution and ozone; A dual-chamber electrolysis system is assembled, consisting of an anode, a composite bipolar membrane, and a cathode, wherein the dual-chamber electrolysis system includes an anode chamber and a cathode chamber; The cathode is a graphite felt cathode supported on a single-atom catalyst; The anode is selected from either Pt / γ-NiOOH / NF anode or NiFeLDH / NF anode; The composite bipolar membrane comprises a commercially available anion exchange base membrane and a perfluorosulfonic acid layer; An alkaline aqueous solution containing biomass is added to the anode chamber; Add the pre-repair electrolyte 2 to the cathode chamber; Constant current electrolysis is performed, and the input charge is calculated based on the total amount of V(IV) in the pre-repaired electrolyte 2. Electrolysis is stopped when the average oxidation state of the electrolyte in the cathode chamber drops to a practical 3.5 valence or other target valence state. The cathode chamber obtains the repaired vanadium redox flow battery electrolyte, and the anode chamber obtains the conversion solution.

[0006] By adopting the above technical solution, and utilizing a homogeneous oxidation combined with a bipolar membrane electrolysis system, the biomass electro-oxidation process replaces the water desorption oxygen process. Therefore, it achieves the effects of eliminating electrolyte valence imbalance, maintaining electrolyte purity, and simultaneously generating chemical products. The specific reaction mechanism is as follows: Step 1: Chemical Oxidation Stage. An oxidizing solution of hydrogen peroxide or a mixture of hydrogen peroxide and ozone is used to oxidize all the unevenly distributed V(III) in the mixed electrolyte to a single V(IV) state. The reduction products of this oxidation process are water and oxygen, eliminating interference from metal ion impurities and carbon source byproducts introduced by solid-phase reducing agents, thus providing a single reactant reference with a clearly defined valence state for subsequent constant-current electrolysis.

[0007] Step Two: Cathode Electrocatalytic Reduction Stage. Under the action of a constant current electric field, a portion of V(IV) in the pre-repaired electrolyte 2 accepts electrons and combines with protons on the graphite felt cathode surface in an acidic environment, transforming into V(III) and water. The single-atom catalyst on the graphite felt surface reduces the charge transfer resistance at the cathode interface. Based on the pre-unified V(IV) concentration, the Faraday input charge is calculated, and an equimolar amount of V(IV) in the solution is quantitatively reduced to V(III), specifically restoring the average valence state of the electrolyte to a practical 3.5 valence, meeting the operational requirements of the vanadium redox flow battery.

[0008] Step 3: Anodic biomass electrocatalytic oxidation stage. An alkaline aqueous solution containing biomass undergoes an electro-oxidation reaction at the anode interface. The electrochemical oxidation thermodynamic potential of biomass molecules is lower than the oxygen desorption potential of water. Under the action of the anode catalyst, the biomass substrate preferentially undergoes dehydrogenation and oxidation transformation, generating corresponding organic acids or ketones. This electrochemical conversion pathway alters the anode-limiting rate step of conventional water electrolysis, reduces the operating voltage of the entire two-chamber electrolysis system, and saves system energy.

[0009] Step Four: Bipolar Membrane Water Dissociation Stage. Under reverse bias, water molecules in the composite bipolar membrane dissociate into protons and hydroxide ions. The protons generated migrate to the cathode chamber to replenish the acidity consumed by vanadium ion reduction, while the hydroxide ions migrate to the anode chamber to replenish the alkalinity consumed by biomass oxidation. The dense structure of the composite bipolar membrane prevents biomass and alkaline substances in the anode chamber from permeating into the cathode chamber, maintaining the isolation of the reactants in the two chambers.

[0010] Preferably, the total vanadium ion concentration in the mixed electrolyte 1 is from 1.0 mol / L to 2.3 mol / L, and it contains free acid with a concentration of 3.0 mol / L to 4.3 mol / L; the free acid is selected from sulfuric acid, hydrochloric acid, and a mixture of sulfuric acid and hydrochloric acid; and the mass concentration of the hydrogen peroxide solution is from 3% to 30%.

[0011] By adopting the above technical solutions, the concentrations of vanadium ions and free acid are limited to ensure that the mixed electrolyte has proton transport capability and electrochemical activity, matching the operating parameters of conventional flow batteries; the concentration of hydrogen peroxide solution is controlled to adjust the oxidation degree of low-valence vanadium ions.

[0012] Preferably, in the alkaline aqueous solution containing biomass, the biomass is selected from glucose, xylose, 5-hydroxymethylfurfural, furfural, vanillin, benzaldehyde, ethylene glycol, and glycerol, and the concentration of the biomass is from 0.1 mol / L to 1.0 mol / L; the alkali in the alkaline aqueous solution containing biomass is selected from sodium hydroxide and potassium hydroxide, and the concentration of the alkali is from 1.0 mol / L to 4.0 mol / L; the constant current density of the constant current electrolysis treatment is 10 mA / cm². 2 Up to 200mA / cm 2 .

[0013] By adopting the above technical solution, organic small molecules are selected as substrates and constant current electrolysis is performed in an alkaline environment to improve the adsorption and dehydrogenation rate of organic molecules on the anode surface; by matching the reactant concentration and constant current density, the occurrence of oxygen desorption reaction of anode moisture is suppressed, and the cell voltage value of constant current electrolysis process is kept stable.

[0014] Preferably, the composite bipolar membrane is prepared by a method comprising the following steps: dissolving perfluorosulfonic acid resin in a solvent to prepare a perfluorosulfonic acid resin solution with a mass concentration of 5% to 25%; the solvent is selected from N,N-dimethylformamide, a mixed solvent of ethanol and water in a volume ratio of 1:1, and dimethyl sulfoxide; the commercial anion exchange base membrane is selected from PiperIONA60, FAB-PK-130, and FAA-3-PK-130; applying the perfluorosulfonic acid resin solution to one side surface of the commercial anion exchange base membrane, and drying and curing to obtain the perfluorosulfonic acid layer with a thickness of 10 μm to 50 μm.

[0015] By employing the above technical solution, a specific solvent is used to dissolve the perfluorosulfonic acid resin and apply it to the surface of the base membrane, ensuring that the thickness of the formed cation exchange layer remains within a specified range. The perfluorosulfonic acid layer of limited thickness provides water dissociation sites, restricts the diffusion of ions in the anode and cathode reaction chambers, and controls the ohmic resistance of the membrane module.

[0016] Preferably, the single-atom catalyst is selected from one of Fe single-atom catalysts, Bi single-atom catalysts, and Co single-atom catalysts; the loading of the single-atom catalyst on the graphite felt is 2 mg / cm³. 2 Up to 10 mg / cm 2 .

[0017] By adopting the above technical solution, transition metals are loaded onto graphite felt in the form of single atoms, providing atomically dispersed catalytic centers, reducing the activation energy for V(IV) to accept electrons and undergo reduction reaction, and improving the Faraday efficiency of the cathode electrolysis process.

[0018] Preferably, when the single-atom catalyst is an Fe single-atom catalyst, the preparation steps of the graphite felt cathode supported on the single-atom catalyst include: pretreating the graphite felt in a mixture of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 3:1, washing and drying to obtain pretreated graphite felt; dissolving ferric nitrate and dicyandiamide in deionized water at a mass ratio of 1:20 to prepare a precursor solution, immersing the pretreated graphite felt in the precursor solution for ultrasonic treatment, removing and drying to obtain impregnated graphite felt; and placing the impregnated graphite felt in a tube furnace and heating it to 800°C under an argon atmosphere for heat treatment to obtain the graphite felt cathode supported on the Fe single-atom catalyst.

[0019] By adopting the above technical solutions, the mixed acid pretreatment increases the oxygen-containing functional groups on the surface of graphite felt and improves the hydrophilicity of the fiber surface; by controlling the mass ratio of ferric nitrate to nitrogen-containing precursor dicyandiamide and the heat treatment temperature, nitrogen atoms are used to coordinate and bond with iron atoms, inhibiting the aggregation of iron atoms during high temperature, and realizing the single-atom-level distribution of catalyst on the surface of graphite felt.

[0020] Preferably, when the single-atom catalyst is a Bi single-atom catalyst, the preparation steps of the graphite felt cathode supported on the single-atom catalyst include: pretreating the graphite felt with mixed acid to obtain pretreated graphite felt; dissolving bismuth nitrate and trimesic acid in a molar ratio of 1:3 in an N,N-dimethylformamide solvent containing nitric acid to obtain a precursor mixed solution; placing the pretreated graphite felt into the precursor mixed solution and performing a solvothermal reaction at 120°C to generate a Bi-MOF precursor, then removing and drying it; and calcining the Bi-MOF precursor at 900°C under nitrogen protection to obtain the graphite felt cathode supported on the Bi single-atom catalyst.

[0021] By adopting the above technical solution, nitric acid is added to the solvent system to inhibit the hydrolysis and precipitation of bismuth ions, and promotes their reaction with trimesic acid to grow into a metal-organic framework precursor. Subsequently, the precursor framework is reconstructed by high-temperature calcination, and bismuth atoms enter the carbon framework structure to form stable catalytic sites.

[0022] Preferably, when the single-atom catalyst is a Co single-atom catalyst, the preparation steps of the graphite felt cathode supported on the single-atom catalyst include: dissolving cobalt acetate and pyrrole monomer in sulfuric acid solution at a mass ratio of 1:15 to obtain an impregnation solution; immersing the graphite felt in the impregnation solution to obtain impregnated graphite felt; adding ammonium persulfate solution with the same molar amount as the pyrrole monomer to initiate the polymerization of the pyrrole monomer on the surface of the impregnated graphite felt fiber; vacuum drying to obtain a coated product; and pyrolyzing the coated product at a high temperature of 900°C under an argon atmosphere to obtain the graphite felt cathode supported on the Co single-atom catalyst.

[0023] By adopting the above technical solution, ammonium persulfate is used to initiate the polymerization of pyrrole monomers on the surface of graphite felt fibers, thereby encapsulating cobalt ions in the polymer structure. After high-temperature pyrolysis treatment, the nitrogen-containing polypyrrole derivative is transformed into a nitrogen-doped carbon network, thus achieving the fixation of the position of cobalt single atoms.

[0024] Preferably, when the anode is a Pt / γ-NiOOH / NF anode, the Pt / γ-NiOOH / NF anode is prepared by a method comprising the following steps: washing the foamed nickel sequentially with hydrochloric acid and deionized water to obtain cleaned foamed nickel; placing the cleaned foamed nickel in a potassium hydroxide solution and performing cyclic voltammetry scanning in a potential range of 1.0V to 1.6V to generate foamed nickel with a γ-NiOOH layer; immersing the foamed nickel with the γ-NiOOH layer in a solution containing chloroplatinic acid, adding sodium borohydride solution for chemical reduction deposition, and washing and drying to obtain the Pt / γ-NiOOH / NF anode.

[0025] By employing the above technical solution, an electrochemical cyclic scanning process is performed on a nickel foam substrate to generate a transition layer structure on its surface. Platinum nanoparticles are then fixed on the surface of this structure layer using a chemical reduction deposition method to increase the electrocatalytic sites on the anode surface and enhance its electro-oxidation activity for biomass molecules.

[0026] Preferably, when the anode is a NiFeLDH / NF anode, the NiFeLDH / NF anode is prepared by a method comprising the following steps: cleaning nickel foam to obtain cleaned nickel foam; dissolving nickel nitrate, ferric nitrate and urea in deionized water at a molar ratio of 3:1:10 to obtain a mixed solution; immersing the cleaned nickel foam in the mixed solution and transferring it to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain reacted nickel foam; cooling, rinsing and vacuum drying the reacted nickel foam to obtain the NiFeLDH / NF anode.

[0027] By adopting the above technical solution, limiting the molar ratio of specific reactants in the mixture and the hydrothermal reaction conditions, and utilizing the alkaline environment provided by urea hydrolysis, metal ions are co-precipitated on the nickel foam skeleton and a layered bimetallic hydroxide crystal phase is grown, providing a highly active electrode surface structure.

[0028] This invention provides a method for repairing coupled high-value conversion of biomass using an all-vanadium redox flow battery electrolyte. It has the following beneficial effects: 1. This invention oxidizes V(III) to V(IV) by adding hydrogen peroxide or ozone mixture to an unbalanced mixed electrolyte. Then, constant current electrolysis is used in the electrolysis system to accurately reduce the average valence state of the cathode electrolyte to a practical valence of 3.5. This chemical homogeneous oxidation combined with electrocatalytic quantitative treatment avoids the problems of metal impurity ions and carbon source residue caused by the traditional addition of solid-phase chemical reducing agents. The repaired electrolyte has high purity and accurate valence distribution, which can restore the initial capacity and long-cycle stability of the vanadium redox flow battery.

[0029] 2. In this invention, an alkaline aqueous solution containing biomass is added to the anode chamber. The electrocatalytic oxidation process of the organic substrate replaces the water desorption oxygen process in the traditional electrolytic repair system. Since the electrochemical oxidation thermodynamic potential of biomass molecules is lower than that of water decomposition, this technical feature changes the anode reaction path and eliminates the interfacial contact resistance fluctuations caused by oxygen bubbles on the electrode surface. The working cell voltage of the system decreases, reducing the overall power consumption of the electrolyte repair process.

[0030] 3. This invention utilizes a composite bipolar membrane to construct a dual-chamber electrolysis system. Under the action of an electric field, protons and hydroxide ions are replenished to the anode and cathode respectively through water dissociation of the bipolar membrane. This structure isolates the acidic vanadium electrolyte at the cathode from the alkaline biomass conversion solution at the anode, preventing cross-contamination of reactants across the membrane. While completing the repair of the full vanadium electrolyte at the cathode, organic acid or ketone conversion solution is simultaneously synthesized at the anode using the same electrical energy input process, thus realizing the combination of battery electrolyte maintenance and high-value utilization of biomass. Attached Figure Description

[0031] Figure 1 The UV-Vis spectrum comparison curves of the pre-repair solution in stage S3 and the repair completion solution in stage S4 are shown. Figure 2 The bar chart shows the molar percentage composition of vanadium ions after electrolysis in stage S4 of Examples 1-3. Figure 3 This is a high-performance liquid chromatography (HPLC) evolution characteristic diagram of the anolyte during the electrolysis process in Example 2; Figure 4 This is a comparison curve of cell voltage-time between Example 2 and Comparative Example 2 during the constant current electrolysis process; Figure 5 200mA / cm 2 Discharge capacity decay curves of four electrolyte samples over 200 cycles at constant current density; Figure 6 A bar chart showing the coulombic efficiency and energy efficiency of each sample during the test period; Figure 7 This is a flowchart of the method of the present invention. Detailed Implementation

[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings, preparation examples, embodiments, comparative examples, and test examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] Preparation Examples 1-3: Preparation Example 1: This preparation example provides a method for preparing a composite bipolar membrane, a modified graphite felt cathode, and a foamed nickel anode for the bipolar membrane electrochemical system of the present invention, including the following steps: (1) Preparation of composite bipolar membrane: Perfluorosulfonic acid resin was completely dissolved in N,N-dimethylformamide (DMF) to prepare a 5% (w / w) perfluorosulfonic acid resin solution. A commercial anion exchange membrane (PiperIONA 60) was selected as the base membrane. The solution was uniformly coated onto the surface of the base membrane using an ultrasonic atomization spraying process and then dried and cured in an 80℃ vacuum oven. The spraying amount was controlled so that the thickness of the final perfluorosulfonic acid layer was 10 μm, thus obtaining the self-made bipolar membrane.

[0034] (2) Preparation of the cathode supported on a single-atom catalyst: Commercial graphite felt was pretreated in a mixed acid solution (concentrated sulfuric acid:concentrated nitric acid = 3:1 volume ratio) at 60°C for 4 hours, then washed and dried. Ferric nitrate (Fe(NO3)3·9H2O) and dicyandiamide (DCDA) were dissolved in deionized water at a mass ratio of 1:20 to prepare a precursor solution. The graphite felt was then immersed in this solution and sonicated for 2 hours. After drying, it was placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under an argon atmosphere and held for 2 hours. Excess nitrogen source was used to anchor iron atoms and prevent agglomeration. The initial iron salt concentration was controlled so that the final loading of the Fe single-atom catalyst on the graphite felt was 2 mg / cm³. 2 Thus, a graphite felt cathode loaded with Fe single atoms is obtained.

[0035] (3) Preparation of the anode electrocatalyst: Commercial nickel foam (NF) was ultrasonically cleaned sequentially with 3M HCl and deionized water for 15 minutes. The cleaned nickel foam was placed in 1M KOH solution as the anode, and 50 cycles of cyclic voltammetry scanning (potential range 1.0–1.6 V vs. RHE) were performed to reconstruct the γ-NiOOH layer on its surface in situ. Subsequently, the nickel foam with the γ-NiOOH layer was immersed in a solution containing 5mM chloroplatinic acid (H2PtCl6), and an excess of fresh 0.1M sodium borohydride (NaBH4) solution was added dropwise for chemical reduction deposition. After washing and drying, the Pt / γ-NiOOH / NF anode was obtained.

[0036] Preparation Example 2: This preparation example provides a method for preparing a composite bipolar membrane, a modified graphite felt cathode, and a foamed nickel anode for the bipolar membrane electrochemical system of the present invention, including the following steps: (1) Preparation of composite bipolar membrane: Perfluorosulfonic acid resin was completely dissolved in a 1:1 volume ratio of ethanol and water to prepare a 15% (w / w) solution. A commercial anion exchange membrane (FAB-PK-130) was selected as the base membrane. The above solution was applied to one side of the base membrane using a doctor blade coater and dried at 60°C. The doctor blade gap of the coater was adjusted to stabilize the thickness of the final perfluorosulfonic acid layer at 30 μm, thus obtaining the self-made bipolar membrane.

[0037] (2) Preparation of the supported single-atom catalyst cathode: Bismuth nitrate (Bi(NO3)3·5H2O) and trimesic acid (BTC) were dissolved in N,N-dimethylformamide (DMF) solvent containing a small amount of nitric acid at a molar ratio of 1:3 (to inhibit the hydrolysis of bismuth ions to form precipitates). The substrate was placed in a graphite felt pretreated with mixed acid and subjected to a solvothermal reaction at 120℃ for 12 hours to grow a Bi-MOF precursor. After drying, it was calcined at 900℃ for 2 hours under nitrogen protection to promote the escape of bismuth atoms and their anchoring in carbon framework defects. By controlling the impregnation time, the final Bi single-atom catalyst loading was achieved to be 6 mg / cm³. 2 Thus, a graphite felt cathode loaded with Bi single atoms is obtained.

[0038] (3) Preparation of the anode electrocatalyst: Nickel nitrate (Ni(NO3)2·6H2O), ferric nitrate (Fe(NO3)3·9H2O), and urea were dissolved in 30 mL of deionized water at a molar ratio of 3:1:10 (the 3:1 ratio of Ni to Fe is a necessary condition for the formation of a stable LDH crystal phase, and excess urea is used as a hydrolysis agent). The cleaned nickel foam was immersed in the mixture and transferred to a polytetrafluoroethylene reactor for hydrothermal reaction at 120 °C for 12 hours. After cooling, the nickel foam was removed, repeatedly rinsed with deionized water and ethanol, and vacuum dried at 60 °C, thus growing a NiFeLDH nanosheet array on its surface in situ, and obtaining the NiFeLDH / NF anode.

[0039] Preparation Example 3: This preparation example provides a method for preparing a composite bipolar membrane, a modified graphite felt cathode, and a foamed nickel anode for the bipolar membrane electrochemical system of the present invention, including the following steps: (1) Preparation of composite bipolar membrane: Perfluorosulfonic acid resin was completely dissolved in dimethyl sulfoxide (DMSO) to prepare a high-concentration viscous solution with a mass concentration of 25%. A commercial anion exchange membrane (FAA-3-PK-130) was selected as the base membrane. The solution was thickly coated onto the surface of the base membrane by multilayer casting. The membrane was then slowly baked in a vacuum oven at 100°C for 12 hours to completely remove the DMSO. After curing, the thickness of the perfluorosulfonic acid layer was controlled to reach 50 μm, thus obtaining the self-made bipolar membrane.

[0040] (2) Preparation of the supported single-atom catalyst cathode: Cobalt acetate (Co(CH3COO)2) and pyrrole monomer were dissolved in 0.5M sulfuric acid solution at a mass ratio of 1:15, and the solution was then impregnated with graphite felt. An equimolar amount of ammonium persulfate (APS) solution was slowly added dropwise to initiate in-situ polymerization of pyrrole on the surface of the graphite felt fibers, uniformly coating the cobalt ions. After vacuum drying, the product was pyrolyzed at 900℃ for 2 hours under an argon atmosphere, anchoring the cobalt single atoms using a nitrogen-doped carbon network derived from nitrogen-rich polypyrrole. This resulted in a final effective loading of 10 mg / cm³ for the Co single-atom catalyst. 2Thus, a graphite felt cathode loaded with Co single atoms is obtained.

[0041] (3) Preparation of the anode electrocatalyst: Using the same cyclic voltammetric electrochemical activation method as in Preparation Example 1, an active transition layer of γ-NiOOH was generated in situ on the surface of nickel foam. The activated nickel foam was used as the working electrode and placed in a high-purity aqueous solution containing 2 mM chloroplatinic acid and 0.1 M sulfuric acid. Platinum complex ions were driven to be reduced and deposited on the surface of γ-NiOOH by a constant potential deposition method (depositing for 200 seconds at a potential of -0.2 V vs. Ag / AgCl). After rinsing with deionized water and drying, the Pt / γ-NiOOH / NF anode was obtained.

[0042] Figure 7 The overall operation flow of the method of the present invention is demonstrated. The flow consists of four consecutive process steps: First, the positive and negative electrolytes of the battery to be repaired are physically mixed (S1). At this time, the mixed electrolyte includes V(III) and V(IV), but the valence states are mismatched. Then, the valence state and concentration of the mixed electrolyte are analyzed to determine the molar concentration ratio of V(IV) to V(III) (S2). Based on the results of the previous determination, an oxidant is added quantitatively to adjust the oxidation and convert V(III) in the system to V(IV) uniformly (S3). Finally, the pretreated electrolyte is introduced into a specially assembled bipolar membrane electrolysis system, and bipolar membrane electrochemical coupling treatment is performed under constant current conditions to simultaneously achieve the valence reduction repair of the cathode vanadium electrolyte and the oxidation conversion of biomass in the alkaline aqueous solution containing biomass at the anode (S4).

[0043] Examples 1-3:

[0044] Example 1 This embodiment provides a method for repairing the electrolyte of a vanadium redox flow battery coupled with high-value conversion of biomass, including the following steps: S1: Electrolyte Mixing: The positive and negative electrolytes (both sulfuric acid-based systems) of the vanadium redox flow battery to be repaired are mixed in a certain proportion to obtain mixed electrolyte 1. Sampling and calibration show that the total vanadium ion concentration in mixed electrolyte 1 is 1.0 mol / L, and it contains free acid selected from sulfuric acid with a concentration of 3.0 mol / L.

[0045] S2: Valence and concentration analysis: The content of vanadium ions in each valence state in mixed electrolyte 1 was determined by using ultraviolet-visible spectroscopy (UV-Vis) combined with potentiometric titration. The molar ratio of V(IV) to V(III) in the mixed solution was calculated to be 1:0.7.

[0046] S3: Oxidation Adjustment: Based on the analysis results of S2, a 3% (w / w) hydrogen peroxide solution was quantitatively and slowly added dropwise to the mixed electrolyte 1 as a green oxidant under continuous mechanical stirring. Utilizing the oxidizing properties of hydrogen peroxide, all V(III) in electrolyte 1 was oxidized to V(IV). The addition was stopped after the solution color completely changed to the bright blue characteristic of V(IV), resulting in a pre-repair electrolyte 2 with uniform valence state.

[0047] S4: Bipolar membrane electrochemical coupling: Assembling a dual-chamber electrolysis system consisting of an anode, bipolar membrane, and cathode. The cathode is a graphite felt supported on a Fe single-atom catalyst prepared in Example 1 (catalyst loading of 2 mg / cm³). 2 The anode is the Pt / γ-NiOOH / NF electrode prepared in Preparation Example 1; the diaphragm is a composite bipolar membrane with a perfluorosulfonic acid layer thickness of 10 μm prepared in Preparation Example 1.

[0048] A 1 mol / L NaOH aqueous solution containing 0.1 mol / L glucose was prepared as an alkaline aqueous solution containing biomass and added to the anode chamber; the pre-repair electrolyte 2 obtained in S3 was added to the cathode chamber as the cathode electrolyte. Constant current electrolysis was performed at a constant current density of 30 mA / cm². 2 Electrochemical treatment was performed under the specified conditions. The total input charge required to reduce half of the vanadium ions was calculated based on the molar amount of V(IV) in the pre-repaired electrolyte 2 and Faraday's law, and this was set as the cutoff capacity. Electrolysis was stopped when the average oxidation state of the cathode electrolyte dropped to a practical valence of 3.5 (V(IV) to V(III) in the solution returned to a 1:1 ratio). The repaired sulfate-based vanadium redox flow battery electrolyte was obtained from the cathode chamber, and the conversion solution rich in the high-value-added product gluconic acid was obtained from the anode chamber.

[0049] Example 2 This embodiment provides a method for repairing the electrolyte of a vanadium redox flow battery coupled with high-value conversion of biomass, including the following steps: S1: Electrolyte Mixing: The imbalanced mixed-acid vanadium redox flow battery positive electrode electrolyte and negative electrode electrolyte are mixed to obtain mixed electrolyte 1. The total vanadium ion concentration in mixed electrolyte 1 is measured to be 1.5 mol / L. It contains free acid, which is selected from a mixture of sulfuric acid and hydrochloric acid, wherein the sulfuric acid concentration is 1.5 mol / L and the hydrochloric acid concentration is 2.0 mol / L (i.e., the total acidity of the system's free acid is 3.5 mol / L).

[0050] S2: Valence state and concentration analysis: The molar ratio of V(IV) to V(III) in mixed electrolyte 1 was accurately determined to be 1:0.9 by potentiometric titration.

[0051] S3: Oxidation Adjustment: Based on the analysis results of S2, a 5% hydrogen peroxide solution was quantitatively added to the mixed electrolyte 1 under stirring, and an appropriate amount of ozone (mixed oxidant) was introduced. The imbalanced V(III) in electrolyte 1 was precisely oxidized to V(IV). The oxidation was stopped when the solution color showed the bright blue characteristic of V(IV), and the pre-repaired electrolyte 2 was obtained.

[0052] S4: Bipolar membrane electrochemical coupling: Assembling a dual-chamber electrolysis system consisting of an anode, a bipolar membrane, and a cathode. The cathode is a graphite felt with a Bi single-atom catalyst supported as prepared in Example 2 (catalyst loading of 6 mg / cm³). 2 The anode is the NiFeLDH / NF electrode prepared in Preparation Example 2; the diaphragm is a composite bipolar membrane with a perfluorosulfonic acid layer thickness of 30 μm prepared in Preparation Example 2.

[0053] A 2.5 mol / L KOH aqueous solution containing 0.5 mol / L furfural was prepared as an alkaline aqueous solution containing biomass and added to the anode chamber; pre-repair electrolyte 2 was added to the cathode chamber. Constant current electrolysis was performed at a constant current density of 30 mA / cm². 2 The system operates as follows: The input charge is precisely calculated and set as the cutoff capacity based on the concentration of V(IV) in the pre-repaired electrolyte 2. The system automatically stops when the input charge reaches the set value and the average oxidation state of the electrolyte in the cathode chamber drops to the practical 3.5 valence. The cathode chamber obtains a thoroughly repaired mixed-acid-based vanadium redox flow battery electrolyte, while furfural in the anode chamber undergoes efficient electrocatalytic oxidation to obtain a conversion solution rich in furoic acid.

[0054] Example 3 This embodiment provides a method for repairing the electrolyte of a vanadium redox flow battery coupled with high-value conversion of biomass, including the following steps: S1: Electrolyte Mixing: The positive and negative electrolytes of the hydrochloric acid-based vanadium redox flow battery to be repaired are mixed to obtain mixed electrolyte 1. The total vanadium ion concentration in mixed electrolyte 1 is measured to be 2.3 mol / L, and it contains free acid selected from hydrochloric acid with a concentration of 4.3 mol / L.

[0055] S2: Valence and concentration analysis: The molar ratio of V(IV) to V(III) in mixed electrolyte 1 was determined by potentiometric titration to be 1:1.2.

[0056] S3: Oxidation Adjustment: Based on the concentration analysis results, a 30% hydrogen peroxide solution was quantitatively added dropwise to the mixed electrolyte 1 under vigorous stirring. The V(III) in the system was completely oxidized and balanced into a single V(IV) state. The process was stopped when the solution turned completely bright blue, thus obtaining the pre-repair electrolyte 2.

[0057] S4: Bipolar membrane electrochemical coupling: Assembling a dual-chamber electrolysis system consisting of an anode, a bipolar membrane, and a cathode. The cathode is a graphite felt with a Co single-atom catalyst supported as prepared in Example 3 (catalyst loading of 10 mg / cm³). 2 The anode is the Pt / γ-NiOOH / NF electrode prepared in Preparation Example 3; the diaphragm is a heavy-duty composite bipolar membrane with a perfluorosulfonic acid layer thickness of 50 μm prepared in Preparation Example 3.

[0058] A high-concentration 4mol / L NaOH aqueous solution containing 1.0mol / L glycerol was prepared and added to the anode chamber as an alkaline aqueous solution containing biomass; a high-concentration pre-repair electrolyte 2 was added to the cathode chamber. Constant current electrolysis was performed under constant current conditions (current density 30mA / cm²). 2 The process is carried out under the following conditions. The input charge is calculated as the cutoff capacity based on the total V(IV) concentration in electrolyte 2. Electrolysis is stopped when the average oxidation state of the electrolyte in the cathode chamber is reduced to a practical valence of 3.5. After the process, a high-concentration hydrochloric acid-based vanadium electrolyte is obtained from the cathode chamber, and a conversion solution rich in high-value-added chemicals (dihydroxyacetone and glyceric acid) is obtained from the anode chamber.

[0059] Comparative Examples 1-3: Comparative Example 1: Compared with Example 2, the difference is that the oxidation adjustment in step S3 and the bipolar membrane electrochemical coupling step in step S4 are omitted. Instead, a traditional chemical reducing agent (oxalic acid) is directly added to the mixed electrolyte 1 obtained in step S1 and blindly adjusted until the average oxidation state of the solution is close to 3.5. All other steps are the same.

[0060] Comparative Example 2: Compared with Example 2, the difference is that no biomass substrate is added to the anolyte prepared in step S4 (i.e., the anolyte is only a 2.5 mol / L KOH aqueous solution of soda ash), and only the conventional oxygen evolution reaction (OER) occurs at the anode, while the rest are the same.

[0061] Comparative Example 3: Compared with Example 2, the difference is that the oxidation adjustment stage of step S3 is completely omitted. That is, the mixed electrolyte 1 with unbalanced valence state and disordered distribution obtained in step S1 is directly put into the electrolytic cell as the cathode liquid, and constant current electrolysis is performed according to theoretical calculation values. Everything else is the same.

[0062] Test Examples 1-5: Test Example 1: Electrolyte samples from Examples 1-3 were taken at the end of stage S3 and at the set cutoff capacity reached in stage S4, with 2.00 mL taken from each sample. Due to the high initial vanadium concentration in the electrolyte, the extracted electrolyte volume was precisely diluted 50 times with deionized water to ensure its absorbance fell within the linear detection range of the UV-Vis spectrometer. The diluted solution was transferred to a 10 mm quartz cuvette, and a full wavelength scan was performed from 300 nm to 1000 nm using deionized water as a reference, recording the position and intensity changes of the system's characteristic absorption peaks.

[0063] The precise valence distribution of the samples was quantitatively determined using an automatic potentiometric titrator. 2.00 mL of undiluted electrolyte was placed in a titration vessel, and 20 mL of 20% (v / v) sulfuric acid solution was added to provide an acidic environment. A calibrated 0.1000 mol / L cerium sulfate standard solution was used as the oxidizing titrant, with a platinum electrode as the indicator electrode and a calomel electrode as the reference electrode.

[0064] Start stirring and slowly add cerium sulfate standard solution. The instrument automatically records the potential change curve as a function of titration volume. For the electrolyte in stage S4, the titration curve shows two distinct potential jumps. Calculate the molar concentration of V(III) based on the volume consumed at the first titration endpoint, calculate the molar concentration of V(IV) based on the volume difference consumed between the first and second titration endpoints, and then convert this to the actual average oxidation state of each system.

[0065] Table 1. Valence state composition and spectral data of electrolytes at each stage in Examples 1-3

[0066] in conclusion: According to the data in Table 1, the maximum characteristic absorption wavelength of Examples 1-3 in the S3 stage is concentrated in the range of 758.5 ​​nm to 761.2 nm, which corresponds to VO 2+ The specific dd-electron transition patterns of hydrated complexes in ions. Combined with... Figure 1 As can be seen, the dark solid line representing the S3 stage exhibits a single strong absorption peak near 760 nm, confirming that V(III) in the solution has been completely leveled to the V(IV) state. Titration data show that the oxidation conversion rate of V(IV) reaches 98.63% to 99.42%, indicating that by controlling the amount of strong oxidant added, the homogeneous chemical oxidation process eliminates the complex mixture of valence states caused by long-term charge-discharge, and directionally and quantitatively converts V(III) into a uniform high-valence state V(IV). 2+ This pre-treatment chemical balancing eliminates the interference of byproducts caused by direct reduction in traditional remediation methods, and establishes a single reactant system with a clearly defined baseline.

[0067] Based on this benchmark, the S4 phase data from each embodiment exhibits high reproducibility. Figure 1 As shown by the light-colored dashed line representing the end point of electrolysis in stage S4, the absorption peak intensity at 760 nm significantly decreased, while a distinct V(III) characteristic absorption peak was newly formed near 400 nm. This directly verifies the occurrence of the electrocatalytic reduction process from the perspective of band transitions. Combined with... Figure 2 It can be known that ( Figure 2 Using the example numbers as the x-axis and the valence state ratio as the y-axis, the solutions of the three different concentration systems all managed to control the internal V(IV) to V(III) ratio close to the 50% theoretical homogeneous target line shown in the figure. Table 1 shows that the measured data indicate that the V(IV) to V(III) molar ratio in each example was controlled within an equimolar distribution range, with the average valence state distribution between 3.492 and 3.513. The small error in the conversion results confirms the accuracy of the process parameters in actual operation, and that the electrocatalytic reduction process at the cathode interface follows Faraday's law.

[0068] The single-atom catalyst supported on the graphite felt reduces the charge transfer resistance on the electrode surface, enabling highly selective use of constant-current input electrons for VOCs. 2+ To V 3+ The single-electron reduction reaction was successfully performed. The large proton consumption required for the reaction did not trigger a dramatic change in interfacial pH or lead to hydrogen evolution side reactions. The bipolar film structure maintained a highly efficient water dissociation rate throughout the process, replenishing protons to the cathode chamber and ensuring the stable and continuous operation of the high-acidity electrochemical kinetics in this region. Overall data confirm that the directional control of the bipolar film-based decoupled electrolysis system possesses the control precision required for engineering applications.

[0069] Test Example 2: Collect the conversion solution samples discharged from the anode chamber in Examples 1-3 when the electrolysis process reaches the set cutoff capacity. Measure 1.00 mL of the reaction solution and add an appropriate amount of 0.5 mol / L dilute sulfuric acid solution to adjust the pH of the system to the range of 2.5 to 3.0 to terminate the chemical reaction in the microenvironment and meet the injection tolerance requirements of the chromatographic column. Dilute the acidified solution to the final volume with ultrapure water and filter using a 0.22 μm polytetrafluoroethylene aqueous microporous membrane to remove any possible detached catalyst particles or large molecular impurities. Collect the filtrate and inject it into a chromatographic sample vial for analysis.

[0070] High-performance liquid chromatography (HPLC) was used to quantitatively analyze the residual substrate and product amounts in the filtrate. The assay system was equipped with a differential refractive index detector and a UV detector, and a column specifically designed for organic acid analysis was used. The assay conditions were set as follows: column temperature 60℃, mobile phase 5 mmol / L dilute sulfuric acid solution, isocratic elution mode, flow rate 0.6 mL / min, and single injection volume 20 μL.

[0071] Prepare standard solutions of glucose, gluconic acid, furfural, furoic acid, glycerol, dihydroxyacetone, and glyceric acid at different concentration gradients. Inject and test under the same chromatographic conditions, record the retention times of characteristic peaks, and plot the external standard method working curve based on the peak areas.

[0072] The sample from the example was injected for testing. The composition of each component in the sample was determined by comparing the retention time with that of the standard. The actual concentrations of the substrate and the corresponding main product after the reaction were calculated using the working curve and the sample peak area integral. The substrate conversion rate was calculated based on the difference between the initial substrate concentration and the residual concentration after the reaction. The Faraday efficiency of the product was calculated based on the ratio of the actual molar amount of the product to the theoretically calculated Faraday charge.

[0073] Table 2. Distribution and efficiency measurement data of anodic biomass conversion products in Examples 1-3

[0074] in conclusion: According to the data in Table 2, the anode substrates in Examples 1-3 all achieved a high degree of consumption during electrolysis. The substrate conversion rate of the furfural system reached 94.7%, while the conversion rates of the glucose and glycerol systems remained at 86.4% and 81.2%, respectively. Figure 3 This paper presents chromatographic comparison data of the anolyte mixture before and after bipolar membrane electrolysis in Example 2 (furfural conversion system). For clear comparison, the pre-reaction curves have been vertically shifted. The dark gray solid line represents the initial solution before electrolysis, exhibiting a large single chromatographic peak at approximately 12 min retention time, corresponding to the added high concentration of furfural substrate. The black solid line represents the anolyte after reaching the set electrolysis capacity. At this point, the furfural characteristic peak area at 12 min has significantly decreased, with only trace amounts remaining; simultaneously, a large main product chromatographic peak appears at approximately 8 min retention time. Comparison with the standard working curve confirms this new peak as the target high-value-added product, furoic acid.

[0075] The stark contrast between the increasing and decreasing peak areas provides direct physicochemical evidence of highly selective and directed oxidation of the substrate. Product distribution indicates that the conversion process is not a disordered degradation; gluconic acid achieved a selectivity of 93.1% in Example 1 and furoic acid achieved a selectivity of 91.8% in Example 2, with the Faradaic efficiency of each target product remaining at a high level. This confirms that most of the charge input at the anolyte is effectively directed to the oxidation, breakage, and recombination processes of specific bonds in the biomass molecules. These test results and chromatograms conclusively verify the feasibility of this scheme, based on a bipolar membrane decoupled electrochemical system, in achieving a pathway substitution mechanism from the anolyte oxygen evolution reaction to the biomass electrooxidation reaction and the occurrence of the biomass electrooxidation reaction mechanism.

[0076] In an alkaline microenvironment, Pt / γ-NiOOH or NiFeLDH catalysts supported on nickel foam substrates exhibit strong adsorption capacity and electrocatalytic dehydrogenation activity for oxygen-containing small organic molecules. Since the electrochemical oxidation thermodynamic potential of biomass molecules is much lower than that of water splitting, the anodic reaction under constant current drive preferentially follows the biomass electrooxidation pathway with less kinetic resistance. The single-component Faraday efficiencies of up to 82.6% and 87.2% shown in Table 2 confirm that, while maintaining 30 mA / cm², the reaction is highly efficient. 2 During the specified current density, the oxygen desorption side reaction of moisture on the anode surface was maximally suppressed, with electron transfer primarily originating from the oxidation process of the organic substrate. Simultaneously, hydroxide ions continuously dissociated from the bipolar membrane migrated directionally into the anode chamber, compensating for the significant alkalinity consumption during the high-concentration substrate conversion process, maintaining the structural stability of the catalyst's active phase and ensuring the continuous occurrence of the reaction. This data confirms that this process, while achieving precise repair of the all-vanadium electrolyte at the cathode, simultaneously synthesizes high-value-added fine chemicals at the anode using the same electrical energy input process, transforming the anode energy consumption in traditional electrolytic repair into economically beneficial material output.

[0077] Test Example 3: The dual-chamber bipolar membrane electrolyzers of Example 2 and Comparative Example 2 were assembled separately. In Example 2, a pre-repair electrolyte was added to the cathode chamber, and a 2.5 mol / L KOH solution containing 0.5 mol / L furfural was added to the anode chamber. In Comparative Example 2, the same volume of pre-repair electrolyte was added to the cathode chamber, and only an equal volume of 2.5 mol / L KOH soda ash solution was added to the anode chamber. Both systems used graphite felt supported on a Bi single-atom catalyst as the cathode and NiFeLDH / NF as the anode.

[0078] Connect the assembled electrolytic cell to the DC regulated power supply and data acquisition system. Under constant temperature water bath conditions of 25℃, set the constant current electrolysis mode and control the operating current density at 30mA / cm². 2 .

[0079] Start the electrolysis unit and simultaneously activate the multi-channel voltage recorder to record the total potential difference across the electrolytic cells. Set the data acquisition frequency to extract real-time voltage values ​​every 10 minutes. Continue electrolysis for 60 minutes, observe the trend of cell voltage changes, and obtain the steady-state cell voltage range. Based on the measured cell voltage differences, calculate the change in system energy consumption per unit time.

[0080] Table 3. Cell voltage measurement data during constant current electrolysis in Example 2 and Comparative Example 2

[0081] in conclusion: Based on the data in Table 3, in Example 2, with furfural substrate, the system cell voltage remained between 1.437V and 1.482V during constant current operation, and the calculated steady-state average cell voltage was 1.455V. In Comparative Example 2, with only soda ash solution in the anode chamber, the system cell voltage ranged from 2.119V to 2.164V, with a steady-state average of 2.140V. (Combined with...) Figure 4 It was demonstrated at 50mA / cm 2 The real-time cell voltage evolution of a two-chamber bipolar membrane electrolysis system under constant current density for 60 minutes is shown in the figure. The dark gray dashed line with a circular mark at the top represents Comparative Example 2, whose anodic process is constrained by the water splitting reaction. Water molecules undergo a four-electron transfer process on the surface of metal hydroxide to generate oxygen. The intrinsic kinetics of this oxygen evolution reaction are constrained, accompanied by extremely high overpotentials, which pushes up the overall cell voltage required to maintain the corresponding current density, keeping it at a high level of approximately 2.140V. At the same time, Comparative Example 2 generates a large amount of oxygen. The continuous generation and desorption of tiny oxygen bubbles within the pores of the nickel foam causes dynamic changes in the contact area at the electrode interface, resulting in a wide fluctuation in the baseline.

[0082] The solid black line with a square mark below represents Example 2. In this example, the introduction of furfural, an oxygen-containing small organic molecule, into the anolyte region facilitates a more thermodynamically efficient biomass electro-oxidation reaction, replacing the oxygen evolution process. The theoretical thermodynamic potential for furfural electrochemical oxidation is lower than that for water decomposition. Under the combined action of the electric field and the NiFeLDH catalyst, furfural molecules preferentially adsorb at the active sites of the catalyst, transforming into furoic acid through dehydrogenation and nucleophilic attack by hydroxyl species. This liquid-phase transformation pathway avoids the high-energy-barrier oxygen-oxygen bond coupling step, forming a new rate-limiting step at the anolyte, thus lowering the operating potential of the anolyte. This reduces the average cell voltage to 1.455V. In Example 2, both reactants and products exist in dissolved form in the electrolyte, eliminating interfacial contact resistance fluctuations caused by gas evolution, reducing the shielding effect of bubbles on the conductive path, lowering the ohmic internal resistance of the system, and resulting in a more stable cell voltage.

[0083] Compare the steady-state tank voltage data, Figure 4 The double-headed arrow and text in the middle visually indicate the 0.685V average system voltage drop. Anodic reaction reconstruction reduced the overall cell voltage of Example 2 by 0.685V compared to Comparative Example 2. Under the same constant input current, the overall system energy consumption was reduced by 32%. Test data demonstrates the technical advantages of this invention in reducing electrolyte remediation energy consumption, confirming that the anodic coupling biomass conversion mechanism reduces the operating energy consumption of traditional electrolyte remediation processes while completing targeted synthesis.

[0084] Test Example 4: The cathode electrolyte from Example 2 after electrolytic repair and the electrolyte from Comparative Example 1 after blind repair using oxalic acid chemical reduction were collected. 5.00 mL of each sample was placed in a volumetric flask and diluted 100 times with 2% (v / v) ultrapure nitric acid solution to reduce the interference of high concentrations of vanadium ions in the matrix on the plasma torch and to meet the sample introduction requirements of the testing instrument.

[0085] The diluted solution was injected into an inductively coupled plasma optical emission spectrometer (ICP-OES), and the concentration of common metal impurity ions such as iron, sodium, potassium, and nickel that are prone to battery side reactions was determined using the internal standard method. Argon was used as the carrier gas and plasma gas during the test.

[0086] Take 5.00 mL of each of the two reconstituted electrolyte solutions mentioned above, filter them through a 0.22 μm glass fiber membrane, dilute them 10 times, and inject them into a total organic carbon (TOC) analyzer. The residual TOC concentration in the system is determined using high-temperature combustion oxidation-nondispersive infrared absorption spectrometry. By recording the signal response values ​​of each sample and combining them with a standard curve, the absolute concentration of impurities in the original electrolyte solution is calculated.

[0087] Table 4. Data on the concentration of impurity elements in the electrolyte after repair in Example 2 and Comparative Example 1

[0088] in conclusion: According to the data in Table 4, the concentrations of various metal impurities in the electrolyte repaired in Example 2 were at extremely low levels, with iron ion concentration at 1.18 mg / L, sodium ion concentration at 3.42 mg / L, and total organic carbon concentration at only 4.28 mg / L. In contrast, the electrolyte repaired in Comparative Example 1 showed higher concentrations of iron ions (42.15 mg / L) and sodium ions (27.63 mg / L), and the total organic carbon concentration reached 1482.50 mg / L.

[0089] In the initial balancing stage of Example 2, an oxidant composed of hydrogen peroxide and ozone was used. The reduction products after oxidizing low-valence vanadium were only water and oxygen, effectively cutting off the entry pathways of external metal impurities and organic matter at the source. During the electrolytic repair stage, the bipolar membrane system achieved dual isolation of the physical space and chemical environment for the anode and cathode reactions. The high-concentration alkaline liquid in the anode chamber and the furfural biomass substrate were blocked by the dense ion exchange layer structure, preventing transmembrane permeation into the cathode chamber. The vanadium ion valence state transformation process in the cathode chamber relied on pure electrons supplied by a constant current input from an external circuit, as well as protons directionally provided by water dissociation at the bipolar membrane interface.

[0090] Comparative Example 1 employed a chemical reduction method involving the direct addition of solid oxalic acid to an acidic vanadium electrolyte to adjust the valence state. Industrial-grade oxalic acid reagents contain trace amounts of inorganic salt impurities such as iron and sodium. These impurities enter the electrolyte system directly along with the reducing agent during addition and accumulate irreversibly during repeated remediation processes. The decarboxylation oxidation process of oxalic acid molecules during the reduction of high-valence vanadium is limited by kinetic resistance at room temperature, resulting in incomplete reactions. This leads to the presence of unreacted carbon source skeletons and intermediate small-molecule organic acids remaining in the electrolyte, manifested in the test results as an abnormally high total organic carbon concentration.

[0091] During long-term operation of vanadium redox flow batteries, high concentrations of metallic impurities such as iron can deposit on the negative electrode surface and act as active sites to catalyze hydrogen evolution side reactions, accelerating electrolyte imbalance. Excessive residual organic carbon molecules in the system are easily physically adsorbed onto the carbon fiber surface of the graphite felt electrode, undergoing electrochemical polymerization or carbonization, blocking vanadium ion mass transfer channels and poisoning electrode catalytic sites. Test data confirms that this process, through a reaction mechanism of pure material input and membrane decoupling, avoids secondary pollution from reducing agents, maintaining high purity of system materials while restoring vanadium ion valence equilibrium.

[0092] Test Example 5: Four vanadium redox flow cells were assembled using freshly prepared standard electrolyte (Sample A), electrolyte repaired in Example 2 (Sample B), electrolyte repaired using oxalic acid chemical reduction in Comparative Example 1 (Sample C), and electrolyte repaired directly by electrolysis in Comparative Example 3 without the pre-oxidation leveling step (Sample D). Each single-cell structure consisted of two graphite felt electrodes heat-treated at 400°C, a perfluorosulfonic acid proton exchange membrane, a flow plate, and a current collector. The effective active area of ​​the electrodes was set to 25 cm². 2 The electrode assembly compression ratio was controlled at 25%. 80 mL of the corresponding electrolyte was taken as the initial positive and negative electrode electrolytes, respectively, and circulated in the battery system by a peristaltic pump at a flow rate of 60 mL / min.

[0093] The assembled single cell was connected to the battery testing system, and charge-discharge tests were conducted at different current densities in a constant temperature environment of 25°C. The charge-discharge voltage cutoff window was set to 0.8V to 1.65V, at 200mA / cm². 2 Pre-charge-discharge cycles were performed at a current density, and the stable coulombic efficiency and energy efficiency values ​​were extracted.

[0094] At a constant current density of 200 mA / cm 2 Under these conditions, four battery systems were subjected to 200 consecutive long-cycle charge-discharge tests. The initial discharge capacity of each battery in the first cycle and the final discharge capacity in the 200th cycle were recorded, and the discharge capacity retention rate after 200 cycles was calculated.

[0095] Table 5. Repair electrolytes of the Examples and Comparative Examples at 200 mA / cm² 2 Battery performance measurement data at current density

[0096] in conclusion: Based on the data in Table 5, combined with Figure 5 and Figure 6 Sample B, using the repair solution from Example 2, exhibited a coulombic efficiency of 96.18%, an energy efficiency of 81.74%, an initial discharge capacity of 1.134 Ah, and a discharge capacity retention rate of 86.86% after 200 cycles. These results are highly consistent with those of Sample A, which used fresh standard electrolyte, in all parameters. Figure 5 In the diagram, the black solid line with circular markings (fresh liquid from sample A) and the dark gray solid line with square markings (repair liquid from Example 2 in sample B) highly overlap and show a gradual decline, confirming that the process of this invention completely restores the battery's stable energy storage baseline. Figure 6 In the comparison of the coulombic efficiency (dark gray bars), which characterizes the ability to prevent short circuits and control side reactions, and the energy efficiency (light gray bars), which characterizes the ability to overcome system internal resistance and polarization, it can be seen that both efficiency indicators of the repair solution (sample B) in Example 2 are maintained at extremely high levels, almost equivalent to those of the fresh standard solution (sample A). Example 2 transforms the disordered vanadium ion valence structure after long-term cycling into a single tetravalent state through a prior homogeneous chemical oxidation process. Based on this determined concentration benchmark, electrochemical calculations show that the macroscopic homogeneity of the cathode electrolyte can be strictly controlled at a valence of 3.5 using quantitative electron input. This dual alignment of physical parameters and chemical valence states allows the repaired vanadium electrolyte to restore the equimolar concentration state required for battery assembly, ensuring that the battery has an initial energy storage capacity comparable to that of the fresh solution, while avoiding the exacerbation of ion cross-leakage by excess species in subsequent cycles.

[0097] Sample D, using the retrieval solution from Comparative Example 3, had an initial volume of only 1.026 Ah, with a volume retention rate decreasing to 74.75%. Figure 5In the diagram, the gray dashed line marked with a triangle represents Comparative Example 3, which did not undergo pre-oxidation. Due to the uneven initial micro-valence states, its overall performance was significantly worse than Example 2. Comparative Example 3 omitted the pre-oxidation leveling process and directly used the measured total V(IV) to V(III) ratio to estimate the electrolyte amount for reduction. The residual local concentration gradient in the unbalanced system caused the electrolysis process to deviate from the ideal state of Faraday equivalent reduction, resulting in the presence of divalent vanadium formed by over-reduction or untouched high-valent vanadium residues within the solution. The deviation of the electrolyte's micro-valence states from the 1:1 ratio directly led to insufficient usable active material, which manifested in the battery operating data as an initial discharge capacity that did not reach the theoretical design value. Furthermore, the residual potential difference accelerated the self-discharge process in subsequent cycles, confirming the necessity of chemical oxidation leveling as a pre-treatment step for restoring the battery's long cycle life.

[0098] The energy efficiency of sample C, using the retrieval solution from Comparative Example 1, decreased to 75.83%, and the capacity retention after 200 cycles decreased to 66.66%. Figure 5 In the diagram, the light gray dotted lines marked with diamonds represent the chemical repair solution used in Comparative Example 1, which was blind-tuned with oxalic acid. Due to the cumulative poisoning from impurities, its initial discharge capacity and cycle life decreased significantly. Comparative Example 1, using a traditional solid-phase reducing agent direct intervention method, introduced inorganic metal ions and unreacted organic carbon chain structures into the system that could not be eliminated through redox reactions. Iron and other impurity metals deposited on the surface of the negative electrode graphite felt fibers altered the local charge distribution at the electrode interface, catalyzing proton reduction to hydrogen gas, disrupting the charge conservation between the positive and negative electrodes, and leading to a decrease in the coulombic efficiency of sample C. The physical adsorption or polymerization of organic impurities under the influence of an electric field covered the active surface area, increasing the battery's ohmic resistance and concentration polarization, and reducing voltage efficiency and energy efficiency. Figure 6 Both Comparative Examples 1 and 3 showed a significant decrease in efficiency, further quantifying the systemic advancement of the membrane isolation and impurity-free process of this invention at the electrochemical, thermodynamic, and kinetic levels. The test results confirm the role of the coupling mechanism between pre-treatment green leveling and bipolar membrane electrolytic reduction in eliminating side reaction inducing factors and restoring long-term cycle stability, demonstrating the scientific validity and closed-loop capability of this scheme in restoring electrolyte performance.

Claims

1. A method for repairing and coupling high-value conversion of biomass with electrolyte in a vanadium redox flow battery, characterized in that, Includes the following steps: The positive and negative electrolytes of the vanadium redox flow battery to be repaired are mixed to obtain mixed electrolyte 1, which includes V(III) and V(IV) but the valence states do not match. The molar ratio of V(IV) to V(III) in the mixed electrolyte 1 was determined; Based on the molar concentration ratio, an oxidant is added to the mixed electrolyte 1 to oxidize V(III) in the mixed electrolyte 1 to V(IV) to obtain the pre-repair electrolyte 2; The oxidant is selected from hydrogen peroxide solution, a mixture of hydrogen peroxide solution and ozone; A dual-chamber electrolysis system is assembled, consisting of an anode, a composite bipolar membrane, and a cathode, wherein the dual-chamber electrolysis system includes an anode chamber and a cathode chamber; The cathode is a graphite felt cathode supported on a single-atom catalyst; The anode is selected from either Pt / γ-NiOOH / NF anode or NiFeLDH / NF anode; The composite bipolar membrane comprises a commercially available anion exchange base membrane and a perfluorosulfonic acid layer; An alkaline aqueous solution containing biomass is added to the anode chamber; Add the pre-repair electrolyte 2 to the cathode chamber; Constant current electrolysis is performed, and the input charge is calculated based on the total amount of V(IV) in the pre-repaired electrolyte 2. Electrolysis is stopped when the average oxidation state of the electrolyte in the cathode chamber drops to a practical 3.5 valence or other target valence state. The cathode chamber obtains the repaired vanadium redox flow battery electrolyte, and the anode chamber obtains the conversion solution.

2. The method for repairing coupled high-value conversion of biomass using an all-vanadium redox flow battery electrolyte according to claim 1, characterized in that, The total vanadium ion concentration in the mixed electrolyte 1 is from 1.0 mol / L to 2.3 mol / L, and it contains free acid with a concentration of 3.0 mol / L to 4.3 mol / L. The free acid is selected from sulfuric acid, hydrochloric acid, and a mixture of sulfuric acid and hydrochloric acid; The mass concentration of the hydrogen peroxide solution is 3% to 30%.

3. The method for repairing coupled high-value conversion of biomass using an all-vanadium redox flow battery electrolyte according to claim 1, characterized in that, In the alkaline aqueous solution containing biomass, the biomass is selected from one of glucose, xylose, 5-hydroxymethylfurfural, furfural, vanillin, benzaldehyde, ethylene glycol, and glycerol, and the concentration of the biomass is from 0.1 mol / L to 1.0 mol / L. The alkali in the biomass-containing alkaline aqueous solution is selected from sodium hydroxide and potassium hydroxide, and the concentration of the alkali is from 1.0 mol / L to 4.0 mol / L. The constant current density of the constant current electrolysis treatment is 10 mA / cm². 2 Up to 200mA / cm 2 .

4. The method for repairing coupled high-value conversion of biomass using an all-vanadium redox flow battery electrolyte according to claim 1, characterized in that, The composite bipolar film is prepared by a method comprising the following steps: Dissolve the perfluorosulfonic acid resin in a solvent to prepare a perfluorosulfonic acid resin solution with a mass concentration of 5% to 25%. The solvent is selected from N,N-dimethylformamide, a mixed solvent of ethanol and water in a volume ratio of 1:1, and dimethyl sulfoxide. The commercially available anion exchange membrane is selected from one of PiperIONA60, FAB-PK-130, and FAA-3-PK-130; The perfluorosulfonic acid resin solution is applied to one side of the commercial anion exchange base membrane, and then dried and cured to obtain the perfluorosulfonic acid layer with a thickness of 10 μm to 50 μm.

5. The method for repairing coupled high-value conversion of biomass using an all-vanadium redox flow battery electrolyte according to claim 1, characterized in that, The single-atom catalyst is selected from one of Fe single-atom catalyst, Bi single-atom catalyst, and Co single-atom catalyst; The single-atom catalyst was loaded at a concentration of 2 mg / cm³ on the graphite felt. 2 Up to 10 mg / cm 2 .

6. The method for repairing coupled high-value conversion of biomass using an all-vanadium redox flow battery electrolyte according to claim 5, characterized in that, When the single-atom catalyst is an Fe single-atom catalyst, the preparation steps of the graphite felt cathode supported on the single-atom catalyst include: The graphite felt was pretreated by immersing it in a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and then washed and dried to obtain pretreated graphite felt. Ferric nitrate and dicyandiamide were dissolved in deionized water at a mass ratio of 1:20 to prepare a precursor solution. The pretreated graphite felt was immersed in the precursor solution and subjected to ultrasonic treatment. The graphite felt was then removed and dried to obtain the impregnated graphite felt. The impregnated graphite felt was placed in a tube furnace and heated to 800°C under an argon atmosphere for heat treatment to obtain the graphite felt cathode supported on the Fe single-atom catalyst.

7. The method for repairing coupled high-value conversion of biomass using an all-vanadium redox flow battery electrolyte according to claim 5, characterized in that, When the single-atom catalyst is a Bi single-atom catalyst, the preparation steps of the graphite felt cathode supported on the single-atom catalyst include: The graphite felt is pretreated with mixed acid to obtain pretreated graphite felt. Bismuth nitrate and pyromellitic acid were dissolved in N,N-dimethylformamide solvent containing nitric acid at a molar ratio of 1:3 to obtain a precursor mixed solution. The pretreated graphite felt was placed in the precursor mixture solution and subjected to a solvothermal reaction at 120°C to generate Bi-MOF precursor, which was then removed and dried. The Bi-MOF precursor was calcined at 900°C under nitrogen protection to obtain the graphite felt cathode supported on the Bi single-atom catalyst.

8. The method for repairing coupled high-value conversion of biomass using an all-vanadium redox flow battery electrolyte according to claim 5, characterized in that, When the single-atom catalyst is a Co single-atom catalyst, the preparation steps of the graphite felt cathode supported on the single-atom catalyst include: Cobalt acetate and pyrrole monomer are dissolved in sulfuric acid solution at a mass ratio of 1:15 to obtain an impregnation solution. The graphite felt is then immersed in the impregnation solution to obtain impregnated graphite felt. Adding an ammonium persulfate solution of the same molar amount as the pyrrole monomer initiates the polymerization of the pyrrole monomer on the surface of the impregnated graphite felt fiber, followed by vacuum drying to obtain the coated product; The coated product was pyrolyzed at 900°C under an argon atmosphere to obtain the graphite felt cathode supported on the Co single-atom catalyst.

9. The method for repairing coupled high-value conversion of biomass using an all-vanadium redox flow battery electrolyte according to claim 1, characterized in that, When the anode is a Pt / γ-NiOOH / NF anode, the Pt / γ-NiOOH / NF anode is prepared by a method comprising the following steps: The foamed nickel was washed sequentially with hydrochloric acid and deionized water to obtain the cleaned foamed nickel. The cleaned nickel foam was placed in a potassium hydroxide solution, and cyclic voltammetry was performed in the potential range of 1.0V to 1.6V to generate nickel foam with a γ-NiOOH layer. The nickel foam with the γ-NiOOH layer was immersed in a solution containing chloroplatinic acid, and sodium borohydride solution was added dropwise for chemical reduction deposition. After washing and drying, the Pt / γ-NiOOH / NF anode was obtained.

10. The method for repairing coupled high-value conversion of biomass using an all-vanadium redox flow battery electrolyte according to claim 1, characterized in that, When the anode is a NiFeLDH / NF anode, the NiFeLDH / NF anode is prepared by a method comprising the following steps: The cleaned nickel foam is obtained by cleaning the nickel foam. Nickel nitrate, ferric nitrate and urea were dissolved in deionized water in a molar ratio of 3:1:10 to obtain a mixed solution. The cleaned nickel foam is immersed in the mixture and then transferred to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain the reacted nickel foam. The reacted nickel foam was cooled, rinsed, and vacuum dried to obtain the NiFeLDH / NF anode.